Analisis Self-Efficacy terhadap Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar Inklusi - Ayu Shinta Dewi; Danuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving ability is an essential competency that students need to develop in mathematics learning. This ability is influenced not only by cognitive factors but also by psychological factors such as self-efficacy. This study aims to analyze the effect of self-efficacy on the mathematical problem-solving ability of students in inclusive elementary schools. This research employed a quantitative approach using an ex post facto design. The sample consisted of 114 students from inclusive elementary schools in Cluster III of Kasihan District, Bantul Regency. Data were collected through a self-efficacy questionnaire and a mathematical problem-solving test. The data were analyzed using descriptive statistics and simple linear regression analysis. The results indicate that self-efficacy has a positive relationship with students’ mathematical problem-solving ability. However, the effect of self-efficacy on mathematical problem-solving ability is not statistically significant (Sig = 0.060 > 0.05). The coefficient of determination shows that self-efficacy contributes 3.1% to students’ mathematical problem-solving ability.